Anthropometric status of nurses working at a private hospital in Pietermaritzburg, KwaZulu-Natal - Leah B. Yegambaram; Kirthee Pillay (AOSIS, 2022)
Background: The prevalence of overweight and obesity among nurses in South Africa (SA) is increasing. This is a concern as overweight and obesity increase the risk for non-communicable diseases (NCDs). Aim: This study aimed to determine the anthropometric status of nurses working at a private hospital and to identify the factors related to a high body mass index (BMI). Setting: This study was conducted at a private hospital in Pietermaritzburg (PMB), KwaZulu-Natal (KZN). Methods: Weight, height and waist circumference (WC) measurements were taken, using standardised procedures. A self-administered questionnaire was developed to collect data on factors associated with a high BMI. Results: Most participants were overweight or obese (86.2%; n = 112). The mean BMI of females (33.55 kg/m2) was significantly higher than that of males (28.08 kg/m2) (p = 0.043). Nurses who did not smoke had a significantly higher BMI (33.84 kg/m2) than those who smoked (29.58 kg/m2) (p = 0.030). Nurses who skipped meals had a higher mean BMI (33.75 kg/m2) than those who did not skip meals (29.63 kg/m2) (p = 0.005). Most females had a WC above 88 cm (66.2%; n = 86), indicating a substantially increased risk for metabolic complications. Conclusion: There was a high prevalence of overweight and obesity among the nurses according to BMI. According to WC, most female nurses had an increased risk for metabolic complications. Being female, not smoking and skipping meals were associated with a higher BMI. Contribution: This study highlights the increasing prevalence of overweight and obesity among nurses.